2021
DOI: 10.1016/j.ajogmf.2021.100401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multidisciplinary shoulder dystocia simulation training on knowledge, performance, and documentation

Abstract: BACKGROUND: Research has shown the utility of simulations involving individuals, yet little data exist on whether communication and documentation are impacted by the integration of all team members into a scenario. In 2018, the obstetrics department at this tertiary hospital began a multidisciplinary team-training simulation for shoulder dystocia. An educational portion was included, teaching a new practice where the provider announces delivery events (head, shoulder, body) to be marked on the delivery record,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, medical documentation of the diagnosis-to-delivery time and obstetrical maneuvers must be accurate, considering maternal counseling following SD and precautions in subsequent pregnancies. Olson et al recently reported a strong correlation between shoulder dystocia training and improved clinical documentation, patient counseling, and communication skills among healthcare providers 29 . Communication skills are significantly correlated with improved clinical performance, suggesting that teamwork improves clinical outcomes in emergencies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medical documentation of the diagnosis-to-delivery time and obstetrical maneuvers must be accurate, considering maternal counseling following SD and precautions in subsequent pregnancies. Olson et al recently reported a strong correlation between shoulder dystocia training and improved clinical documentation, patient counseling, and communication skills among healthcare providers 29 . Communication skills are significantly correlated with improved clinical performance, suggesting that teamwork improves clinical outcomes in emergencies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that residents reported receiving ~ 17 ~ adequate didactic training on the management of shoulder dystocia, however, this did not translate to feelings of independent clinical competence. In the current educational system for residents, simulation and drills have become a proxy for clinical exposure to infrequent obstetric events [10] . The American College of OB/GYN currently advocates for simulation exercises in an attempt to reduce the complications associated with shoulder dystocia [11] .…”
Section: Discussionmentioning
confidence: 99%
“…The pH in the fetal circulation decreases by 0.01–0.04 units/min. In general, the obstetrician typically has approximately 5 min, assuming the fetus is well-oxygenated, before the risk of severe hypoxia arises [ 2 , 33 , 34 , 35 ].…”
Section: Pathophysiology Of Shoulder Dystociamentioning
confidence: 99%